Corporate venture capital in the automotive sector - James P. Gavigan; Peter Fákó; Ramón Compa\~nó (European Commission, Joint Research Centre (JRC), 2024)
The ongoing transformation of the automotive sector is in part driven by factors such as the unrelenting onslaught of electric/hybrid powertrain technologies, in-vehicle and networked software applications, rising demand for electric vehicles, and the emergence of new entrants like Tesla and others notably in China. The response of automotive firms to these challenges includes, inter alia, Open Innovation (OI) tools and strategies of which Corporate Venture Capital (CVC) is one element. CVC investments by large automotive companies are globally spread, but there is a clear concentration of these investments in the US, particularly in California. The vast majority of CVC investments in startups are made in conjunction with other coinvestors, reflecting the high-risk nature of the innovative technologies being developed. Newcomers to the automotive industry, such as Tesla and BYD, are primarily beneficiaries of venture capital financing, including corporate VC, rather than themselves engaging in venture financing. Despite a drop in CVC in 2023, the rising trend in automotive CVC may return over the medium to long term, driven by increasing startup activity in automotive-relevant areas.
Keywords: 330; Automotive industry; Venture capital; Open innovation; Kfz-Industrie; Risikokapital; Open Innovation; Welt